AN ANALYSIS OF STUDENTS’ ABILITY IN PRONOUNCING INTERDENTAL AND POST-ALVEOLAR FRICATIVE CONSONANTS - Nadia Putri; Yuli Herman; Riyen Permata (IdeBahasa, 2026)
This research is motivated by students’ difficulties in distinguishing and pronouncing English dental (/θ/, /ð/) and post-alveolar (/ʃ/, /ʒ/) fricative consonants, which are often influenced by first language interference. This study aims to analyze students’ ability to distinguish and pronounce dental and post-alveolar fricative consonants and to identify the most problematic sounds experienced by students. This research employed a quantitative descriptive method. The subjects of this study were 12 sixth-semester students of the English Education Study Program at Mahaputra Muhammad Yamin University in the 2024/2025 academic year, selected using total sampling technique. The data were collected through a pronunciation test consisting of 20 pairs of words, supported by audio and video recordings. The data were analyzed using scoring rubrics and descriptive statistical analysis to determine students’ pronunciation accuracy. The results showed that students’ overall ability in pronouncing fricative consonants was categorized as good, with an average score of 3.35. The sound /ʃ/ was relatively easier for students to pronounce, while /θ/, /ð/, and /ʒ/ remained problematic due to first language interference. Therefore, more intensive and varied pronunciation exercises are recommended to improve students’ pronunciation accuracy.